1975
DOI: 10.1093/nar/2.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molecular weight of DNA on the determination of anti-DNA antibodies in systemic lupus erythematosus (SLE) sera by radioimmunoassay

Abstract: Using a radioimmunoassay (RIA) based on the Farr technique with radioactively labeled 3-H-DNA for quantitative measurements of anti-DNA antibodies in sera of patients with systemic lupus erythematosus (SLE), the influence of molecular weight of DNA (ranging from 0.1 times 10-6 to 22.0 times 10-6 daltons) on binding and precipitation in this system has been investigated. Comparing our results with mathematical models it follows that one antibody molecule is fixed on the average to a statistical DNA segment of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

1977
1977
1979
1979

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
(10 reference statements)
0
14
1
Order By: Relevance
“…We do not agree with the suggestion of Geisert et al (20) that only DNA of "sufficiently" high molecular weight will allow reliable results by the NH,SO, assay. Since normal sera are just as sensitive to DNA size as SLE sera, high molecular weight DNA limits the potential range of the assay by increasing the background level of binding.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We do not agree with the suggestion of Geisert et al (20) that only DNA of "sufficiently" high molecular weight will allow reliable results by the NH,SO, assay. Since normal sera are just as sensitive to DNA size as SLE sera, high molecular weight DNA limits the potential range of the assay by increasing the background level of binding.…”
Section: Discussioncontrasting
confidence: 99%
“…Effect of DNA Molecular Weight on Anti-DNA Level. Previous studies have demonstrated that the observed anti-DNA level increases as the molecular weight of the DNA increases (10,20,21). The difficulty in completely explaining this phenomenon by application of the Poisson distribution (see Discussion) prompted us to extend the observations to a greater number of SLE sera as well as to normal sera.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Such variations give rise to enormous fluctuations of DNA binding values (6,12). Because in longitudinal studies a proper quantitation of anti-dsDNA is essential, such fluctuations have to be controlled by using DNA with a homogeneous molecular weight or alternatively by correcting variations via the introduction of a panel of standard sera (21).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that suggests that the high salt concentration used in the assay may cause dissociation of all but those complexes that contain the highest avidity antibodies (1 8). In addition, it is now recognized that this method is most applicable in the study of the binding of antibodies to high molecular weight DNA (19,20). Recent evidence suggests that low molecular weight DNA may in fact play a significant role in the pathogenesis of SLE (21,22).…”
mentioning
confidence: 99%